Behavior changes in humans with toxoplasmosis - Esperança, Mariana Fachini [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Cruz, Breno Cayeiro [UNESP]; Prando, Luciana [UNESP]; Lisboa, Natália Donegá [UNESP]; Lopes, Welber Daniel Zanetti; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2017)
Toxoplasma gondii is an intracellular protozoan responsible for toxoplasmosis, a disease which affects different species of birds and mammals, including men. Felids are the only definitive hosts of this parasite, with domestic cats being primordial representatives in the maintenance of T. gondii life cycle in urban environments. Humans can get toxoplasmosis especially by ingestion of tissue cysts present in raw or undercooked meat, through sporulated oocysts present on the environment, or by means of congenital transmission. Different published studies have recently assigned the capability of T. gondii to mediate behavioral changes in animals and humans. In mice with toxoplasmosis, behavior changes were observed in their defense and escape instincts, especially against feline predators, increasing chances of contaminated rodents being eaten, therefore completing the parasite's cycle in the definitive feline host. Studies performed in humans highlighted personality changes and reduction in the response time of stimuli, with an inclination of people positive for toxoplasmosis to traffic accidents, work accidents, suicide, Obsessive Compulsive Disorder (OCD), Parkinson's disease, Alzheimer's disease, Bipolar Disorder, Epilepsy and Schizophrenia being reported. Although many studies point to the existence of behavior modifications mediated by T. gondii in human beings, such inferences are still not entirely understood, reinforcing the need for more researches with methodologies that allow definitive conclusions regarding such theme.
Keywords: Bipolar disorder; Schizophrenia; Toxoplasma gondii; Transmission